“Lezibian/mulezi”: Adoption of “globalized” lesbian identity and secondary self-labels among same-sex attracted women in Harare - Muparamoto, Nelson (Journal of Lesbian Studies, 2022)
Drawing from ethnographic research, incorporating informal conversations, semi-structured interviews and a focus group discussion, the paper explores the subjective meanings and construction of the “lesbian” identity in a “hostile” environment among selected same-sex attracted women in Harare. While the globally circulating identity labels are loaded with historical baggage which can be limiting or confusing in non-western contexts, most of the study participants related to some of the labels that are prominent in the present-day, western-inspired global discourse on same-sex relations. Self-styling and the quest to exhibit masculine decorum was a central aspect in the narratives of most “butch” identifying women. For most butch identifying women being lesbian was closely interwoven with considerations about one’s gendered self. However not all participants were comfortable with the circulating identity labels as they found them restrictive and loaded. While subjective preferences of the participants demonstrate complexity in how “lesbianism” is locally constructed and experienced, the lesbian identity is certainly not obsolete in Harare among same-sex attracted women.
Keywords: afrique; butch; corps; personnes lesbiennes; ressource en ligne; régions géographiques; sexualité; thématiques; zimbabwe

Eau douce: roman - Emezi, Akwaeke (Du monde entier, 2020)
Au Nigéria, dans la cosmologie igbo, lorsqu'un enfant est dans le ventre de sa mère, il est façonné par des esprits qui déterminent son destin. Mais à la naissance de la petite Ada, les portes entre le monde des humains et celui des esprits se sont temporairement ouvertes, le temps pour ces derniers de s'immiscer dans le corps de la fillette et de s'y trouver bloqués. Un pied dans le monde des vivants, un pied dans le monde des esprits, Ada va ainsi grandir envahie par un cortège de voix qui vont se disputer le contrôle de sa vie, fractionnant son être en d'innombrables personnalités.Mais lorsqu'Ada quitte son berceau géographique pour faire ses études aux États-Unis, un événement traumatique d'une violence inouïe va donner naissance à un nouvel esprit, beaucoup plus puissant, beaucoup plus dangereux. Ce nouveau "moi" prend possession d'elle et se nourrit de ses désirs, de sa colère et de sa rancoeur. La vie de la jeune fille prend alors une tournure de plus en plus inquiétante, où la mort semble devenir une séduisante échappatoire. (decitre.fr)
Keywords: afrique; arts; corps; cours; discipline; igbo; lit4700; littérature; nigeria; premier cycle; roman; régions géographiques; thématiques; études littéraires

Empowerment as a disabled, black woman - Oliver, Kym; Abdullahi, Jumoke (2020)
The dynamic duo of Jumoke and Kym tackle the topic of empowerment and what that means for disabled, Black women. This was filmed as part of a TEDx talk at the University of Sussex in England. _______________________________________________________________________________________________ TRIPLE CRIPPLES was created by @TheKymOliver & @JayOnLife to provide a platform for & highlight the narratives of Black & non-Black Women, Femmes & Non-Binary people of colour, living with disabilities. We are here. We exist! We know the media and mainstream disability conversations would have you believe otherwise mega eye roll*... But guess what? WE GOTS THA INTERNETS, BITCHEZZZZ!!! Eat it. *put on shades and look cool at night ———————————————————————————————- JOIN US ON OUR JOURNEY! Hit the comments box! And if you or any women/femmes/non-binary people you know, would like to be a guest... Hit the DM’s! 🖤 Website: https://thetriplecripples.uk/ Twitter/Instagram: @TripleCripples Follow Jumoke: @JayOnLife Follow Kym: @TheKymOliver ———————————————————————————————- Track: “runaway” ~ K15 feat. AMA LIVE! Big Love to K15 for kindly letting us use his amazing music as our bedding track!!! Check out @k15music, support his sound, buy some vinyls and follow him on all platforms: Twitter: @K15music Facebook: @K15music Soundcloud: @K15 Bandcamp: @K15music
Keywords: 2000 à aujourd'hui; afrique; amériques; approches et analyses; capacitisme; caraïbes; corps; cours; discours dominant; empowerment; europe; fem3300; femmes* noires; invisibilité; militance; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; systèmes d'oppressions; thématiques